Analysis of Biomarkers Within the Initial 2 Years Posttransplant and 5-Year Kidney Transplant Outcomes: Results From Clinical Trials in Organ Transplantation-17. Issue 4 (April 2018) - Faddoul, Geovani; Nadkarni, Girish N.; Bridges, Nancy D.; Goebel, Jens; Hricik, Donald E.; Formica, Richard; Menon, Madhav C.; Morrison, Yvonne; Murphy, Barbara; Newell, Kenneth; Nickerson, Peter; Poggio, Emilio D.; et al.
Abstract : Background: An early posttransplant biomarker/surrogate marker for kidney allograft loss has the potential to guide targeted interventions. Previously published findings, including results from the Clinical Trials in Organ Transplantation (CTOT)-01 study, showed that elevated urinary chemokine CXCL9 levels and elevated frequencies of donor-reactive interferon gamma (IFNγ)-producing T cells by enzyme-linked immunosorbent spot (ELISPOT) assay associated with acute cellular rejection within the first year and with lower 1-year posttransplant estimated glomerular filtration rate (eGFR). How well these biomarkers correlate with late outcomes, including graft loss, is unclear. Methods: In CTOT-17, we obtained 5-year outcomes in the CTOT-01 cohort and correlated them with (a) biomarker results and (b) changes in eGFR (Chronic Kidney Disease Epidemiology Collaboration formula) over the initial 2 years posttransplant using univariable analysis and multivariable logistic regression. Results: Graft loss occurred in 14 (7.6%) of 184 subjects 2 to 5 years posttransplant. Neither IFNγ ELISPOTs nor urinary CXCL9 were informative. In contrast, a 40% or greater decline in eGFR from 6 months to 2 years posttransplant independently correlated with 13-fold odds of 5-year graft loss (adjusted odds ratio, 13.1; 95% confidence interval, 3.0-56.6), a result that was validated in the independent Genomics of Chronic Allograft Rejection cohort (n = 165; adjusted odds ratio, 11.2). Conclusions: We conclude that although pretransplant and early posttransplant ELISPOT and chemokine measurements associate with outcomes within 2 years posttransplant, changes in eGFR between 3 or 6 months and 24 months are better surrogates for 5-year outcomes, including graft loss. Abstract : This retrospective analysis data from the Clinical Trials in Organ Transplantation study suggests that changes in eGFR within the first 2 years after transplantation, but not urinary chemokine CXCL9 and donor-reactive interferon gamma-(IFNg)-producing T cells, are associated with graft loss at 5 years.